A Comparison between single field nonmydriatic color fundus photography interpreted by family physicians and dilated indirect ophthalmoscopy by ophthalmologists in diabetic retinopathy screening - Attaya Limwattanayingyong (Chulalongkorn University, 2014)
Thesis (M.Sc.)--Chulalongkorn University, 2006